ANALISIS PENGARUH LIKUDITAS, LEVERAGE, KEPEMILIKAN MANAJERIAL, KOMISARIS INDEPENDEN, UKURAN PERUSAHAAN DAN CORPORATE SOCIAL RESPONBILITY TERHADAP AGRESIVITAS PAJAK (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia 2013-2015) - Dita Ratnasari Suyono, 13.05.52.0070; Nuswandari, Cahyani (Students Journal of Accounting and Banking, 2017)
The purpose of this research is to analyze the effect of liquidity, leverage, managerial ownership, independent commissioner, company size, and Corporate Social Responsibility to the aggressiveness of tax on manufacturing companies listed in Indonesia Stock Exchange 2013-2015 period. Data used in this research is secondary data, the data in this study were obtained from the Financial Statements, Annual Report, ICMD (Indonesian Capital Market Directory) 2013-2015. The sampling method used is purposive sampling. The amount of data that is processed as many as 159 companies. Methods of data analysis using multiple linear regression. The results of research showed that managerial ownership and firm size has a positive and significant tax aggressive, while variable liquidity, leverage, independent commissioners, and Corporate Social Responsibility no significant effect on tax aggressive.Keywords:Â Tax Aggressive, Liquidity, Leverage, Managerial Ownership, Independent Commissioner, Company Size, and Corporate Social Responbility